Degradation and Reliability Analysis of a Circuit Board Based on Accelerated Degradation Test - YIN Chao; ZHOU Guifa; WANG Xu; DU Shaohua (Kongzhi Yu Xinxi Jishu)
At present, accelerated degradation test research is carried out mostly for single stress condition, while the products are faced with an operating condition of many environmental stresses in the field. This paper presented a data modeling method and analysis process for accelerated degradation test under multi-stress, and designed an accelerated degradation test scheme for temperature and humidity comprehensive stress for a control circuit board. Based on the first application of stability test in time series analysis and accelerated degradation test under multi-stress condition, it can be concluded that the parameters of the control board are not degraded under both test and field conditions.